2023
DOI: 10.30935/cedtech/12921
|View full text |Cite
|
Sign up to set email alerts
|

TPACK-SAMR digital literacy competence, technostress, and teaching performance: Correlational study among EFL lecturers

Abstract: This study aimed to scrutinize the correlation between English as a foreign language (EFL) lecturers’ digital literacy competence (DLC) based on the TPACK-SAMR framework and their technostress. In addition, this study revealed how the variables correlated to the lecturers’ EFL teaching performances. Therefore, a correlational design with a descriptive explanation model was conducted. The participants were six EFL lecturers from six different universities in various cities in East Java Province, Indonesia. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Therefore, teachers are unable to implement pedagogical content knowledge properly. Factors that influence include teachers not designing lesson plans, teachers not adapting learning strategies to student characteristics, not conducting curriculum reviews to suit student needs, and a lack of knowledge of English itself (Ball et al, 2008;Muslimin et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, teachers are unable to implement pedagogical content knowledge properly. Factors that influence include teachers not designing lesson plans, teachers not adapting learning strategies to student characteristics, not conducting curriculum reviews to suit student needs, and a lack of knowledge of English itself (Ball et al, 2008;Muslimin et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The abilities that must be possessed by the teacher include knowledge they have and how to implement learning, which means that the understanding and implementation of pedagogical content knowledge must be aligned (Le et al, 2018;Öz, 2014;Safitri et al, 2019). Pedagogical content knowledge consists of pedagogical knowledge and content knowledge, pedagogical knowledge includes aspects of curriculum development, student characteristics and learning objectives, while content knowledge is the knowledge that teachers have about the subjects taught (Lyublinskaya & Kaplon-Schilis, 2022;Muslimin et al, 2023;Sintawati & Abdurrahman, 2020). According to previous study content knowledge in English consists of 2 important points, namely language awareness which includes how the teacher pays attention to the importance of correcting errors that occur in the use of English and language proficiency which includes the teacher's knowledge of grammar, tenses and verbal delivery and non-verbal (Muslimin et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The attendance of mobile technology to mediate teaching and learning of any language gained in numbers lately (Bachore, 2015), especially due to the popularity of the 21 st -century education trend where digital technology literacy becomes one of the students' essential skills to possess, the introduction to 4.0 industrial revolution that requires students to be globally competitive with technology (Lu & Cutumisu, 2022;Muslimin et al, 2023), and the benefits of technology implementation to mediate teaching and learning challenges (Chen et al, 2020). Then, this research showed the attempts of a Balinese language teacher in a primary school to try using an android application that is downloadable for mobile phones to mediate the students' challenges in learning the Balinese language.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its functionality, technology attends various language learning contexts, i.e., in the classroom, outside the classroom, during the project, when the learners' are doing their tasks, and even when the learners are enjoying their relaxed learning time. Hence, many educators take these benefits by employing technology to mediate their language teaching (Muslimin et al, 2023) and boost their students' language learning.…”
Section: Introductionmentioning
confidence: 99%